Evaluating training context competence of use: Productive and unproductive models of use. (June 2015) - Esposito, Giovanna; Freda, Maria Francesca
Highlights: Data analysis pointed to three models of use: Opaque, Learning, Development . The Development Model showed a significant association with Competence of Use. Competence of Use is a reflexive ability in using training resources. There is a need to design evaluation programs directed to sense-making process. Abstract: This study discusses an evaluation model carried out in vocational training contexts and draws from a line of studies that have analyzed the processes of meaning construction according to a semiotic and contextual perspective (Freda, 2011; Freda & De Luca Picione, 2014; Salvatore & Freda, 2011; Salvatore & Venuleo, 2008; Valsiner, 2007 ). The study aims to identify models of use of training contexts (thought of as different ways to give meaning to the relationship between the trainee and the training context), as well as to analyze their relationship with social–demographic variables and course type. An additional aim is to investigate training outcomes to discern any connection existing between models of use and competence of use (e.g. the ability of trainees to participate and benefit from the training setting for their professional development aims). An especially designed ad hoc open-answer questionnaire was administered to 76 trainees in the ex-post impact training phase. We adopted a multi-method analysis methodology (Bolasco, 1999 ). Data analysis pointed to three models of use: Opaque, Learning, Development. The last one showed a significant association with training outcomes which were effective and useful to hypothesize the development of a competence of use. The results have interesting implications for the design of evaluation programs directed to the sensemaking processes that organize the relationship between the formative self and the training context.